(untitled) (Medico Legal Update, 2021)
Indigenous peoples in Indonesia have a diverse family system, this leads to diversity in the devolution system. This form of parental kinship applies to the people of Berbah Sub-District of Sleman Regency. And whoath is in the heavens and the earth, and who is in the heavens and the earth, and who is in the heavens and the earth, and who is in the heavens and the earth, and whoth in the heavens and the earth, and currently, the people in Berbah Sub-District of Sleman Regency are predominantly Muslim, which could potentially influence the pattern of setting inheritance distribution in Islamic Law. There is still a strong principle of togetherness, the principle of deliberation, and the principle of benefit in the order of life of the people of Berbah District of Sleman Regency. Most importantly, they can accept the results of deliberation while upholding the principle of harmony